2003
DOI: 10.1212/01.wnl.0000031424.51127.2b
|View full text |Cite
|
Sign up to set email alerts
|

Tremor in Parkinson’s disease and serotonergic dysfunction

Abstract: These findings support previous indirect evidence that serotonergic neurotransmission is decreased in PD in vivo. The authors hypothesize that the reduction in raphe 5-HT(1A) binding represents receptor dysfunction or loss of cell bodies due to Lewy body degeneration in PD, or both. An association between 5-HT(1A) receptor availability in the raphe and severity of parkinsonian tremor was also found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(165 citation statements)
references
References 29 publications
12
148
2
3
Order By: Relevance
“…In some studies with [ 11 C ]WAY (Rabiner et al, 2002;Doder et al, 2003;Turner et al, 2005), as many as 10% of the subjects were excluded because of abnormally high cerebellar time-activity curves potentially caused by specific binding in cerebellum, incorrect segmentation of cerebellum, or variable properties of the tracer. One of the known properties of [ 11 C]WAY is the very rapid metabolism in the circulation (Gunn et al, 1998;Osman et al, 1998), which may violate the underlying assumption of continuous exchange of brain tissue with circulation and thereby may induce biases to the results of previously applied kinetic models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies with [ 11 C ]WAY (Rabiner et al, 2002;Doder et al, 2003;Turner et al, 2005), as many as 10% of the subjects were excluded because of abnormally high cerebellar time-activity curves potentially caused by specific binding in cerebellum, incorrect segmentation of cerebellum, or variable properties of the tracer. One of the known properties of [ 11 C]WAY is the very rapid metabolism in the circulation (Gunn et al, 1998;Osman et al, 1998), which may violate the underlying assumption of continuous exchange of brain tissue with circulation and thereby may induce biases to the results of previously applied kinetic models.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle abnormalities in the availability of [ 11 C]WAY-binding sites were reported in clinical PET studies of personality differences (Borg et al, 2003), depression (Drevets et al, 1999;Bhagwagar et al, 2004;Sargent et al, 2000), schizophrenia (Tauscher et al, 2002), juvenile myoclon epilepsia (JME) (Meschaks et al, 2005), bulimia nervosa (Tiihonen et al, 2004), ALS (Turner et al, 2005), and Parkinson's disease (PD) (Doder et al, 2003). Together, these studies show that [ 11 C]WAY binding, as an index of serotonin 5HT 1A receptor availability, is correlated with scores of personality, increased in specific cortical regions of patients with schizophrenia and bulimia nervosa, globally decreased in patients with depression and ALS, and focally decreased in patients with JME and in the raphé nucleus of PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of clinical and basic studies, the neural substrate for this motor complication remains unclear. The causative role of 5-HT in tremorgenesis has been strengthened by a recent PET study in PD patients (Doder et al, 2003). Interestingly, these authors showed that severity of parkinsonian tremor, but not rigidity or bradykinesia, was correlated significantly with this decrease in midbrain raphe 5-HT 1A binding, likely reflecting a dysfunction and loss of serotonergic cell bodies early in the disease process (Doder et al, 2003).…”
Section: Role Of 5-ht In Parkinsonian Resting Tremormentioning
confidence: 99%
“…The causative role of 5-HT in tremorgenesis has been strengthened by a recent PET study in PD patients (Doder et al, 2003). Interestingly, these authors showed that severity of parkinsonian tremor, but not rigidity or bradykinesia, was correlated significantly with this decrease in midbrain raphe 5-HT 1A binding, likely reflecting a dysfunction and loss of serotonergic cell bodies early in the disease process (Doder et al, 2003). This evidence is in agreement with the suggested hypothesis of 'disequilibria' in the 5-HT-histamine system responsible for tremor (akathisia), whereas 'disequilibria' in the DA-ACh system might lead to rigidity (akinesia) (Barbeau, 1962).…”
Section: Role Of 5-ht In Parkinsonian Resting Tremormentioning
confidence: 99%
“…PET with [ 11 C]WAY100635, a selective marker of 5-HT 1A receptors, found that the midbrain raphe 5-HT 1A binding was reduced by 27% in PD patients compared to healthy controls and there was a significant correlation between reductions in midbrain raphe 5-HT 1A binding and the severity of tremor (Doder, Rabiner, Turjanski, Lees, & Brooks, 2003). PD patients with tremor-dominant phenotype had significant reductions in [ 11 C]DASB binding in caudate, putamen, raphe nuclei, thalamus, and Brodmann areas 4 and 10 compared with those who had akinetic-rigid PD and with a group of normal controls .…”
Section: Serotonergic Systemmentioning
confidence: 99%